Metacognition as a Predictor of Improvements in Personality Disorders - Carcione, Antonino; Riccardi, Ilaria; Bilotta, Elena; Leone, Luigi; Pedone, Roberto; Conti, Laura; Colle, Livia; Fiore, Donatella; Nicolò, Giuseppe; Pellecchia, Giovanni; Procacci, Michele; Semerari, Antonio (Frontiers in Psychology, 2019)
Personality Disorders (PDs) are particularly hard to treat and the rate of dropout is high. Several authors agree that the psychotherapy could be more successful when it focuses on the core of personality pathology. For this matter therapists dealing with PDs need to understand the psychopathological variables that characterize this pathology and that contribute to maintain the psychopathological processes, finding treatments focused on them to remove obstacles to their efficacy. These observations call for a remarkable effort on what possible mechanism of change psychotherapy should focus on. Several authors pointed out that one key problem that characterizes all PDs is an impairment in understanding mental states, here termed ‘metacognition’, and it could also make the therapy fail. Unfortunately, only a limited number of studies have investigated the role of mentalization in the process of change during psychotherapy. In this paper we assume that poor metacognition corresponds to a core element of the general pathology of personality and its functioning impacts on a series of clinical variables, generating symptoms and interpersonal problems, and on treatment making the psychotherapy slower and less effective. We explore if changes in the ability to reflect and reason about mental states (i.e. metacognition) predict the improvement of different psychopathological variables characterizing PDs. 132 outpatients treated at the Third Center of Cognitive Psychotherapy of Rome followed a structured path tailored for the different psychopathological variables emerging from a wide psychodiagnostic assessment that considers over the symptoms (SCL 90-R), the metacognitive abilities (MAI), the interpersonal relationship (IIP-47), the personality psychopathology (SCID-II complete), the global functioning (GAF). The measurements are repeated after 1 years of treatment. The results show that, as hypothesized, changes in metacognitive abilities predict improvements of the analyzed variables.